When can gravity path-entangle two spatially superposed masses? - Marletto, C; Vedral, V (American Physical Society, 2018)
An experimental test of quantum effects in gravity has recently been proposed, where the gravitational field's ability to entangle two masses is used as a witness of its quantum nature. Here, we discuss what existing models for coupled matter and gravity predict for this experiment. Collapse-type models, and also quantum field theory in curved spacetime, as well as various induced gravities, do not predict entanglement generation; they would, therefore, be ruled out as fundamental descriptions of gravity if entanglement were observed. Instead, local linearized quantum gravity models predict that the masses can become entangled. We analyze the mechanism by which entanglement is established in such models, modeling a gravity-assisted two-qubit gate.